Dynamic venting simulation of valve chambers at both ends of supercritical CO2 pipelines with topographic relief - Bing YAN; Bohui SHI; Junwen CHEN; Xiaoyong TANG; Linfeng ZAN; Yanjing WANG; Yupei LI; Jing GONG (You-qi chuyun)
bjective Carbon capture, utilization and storage (CCUS) is essential for achieving carbon neutrality, in which the safety and efficiency of CO2 transmission plays a vital role. The pipeline transmission of CO2 in the supercritical phase has been widely applied internationally and China has basically mastered the rules to the process of supercritical CO2 pipelines steady-state transmission. However, further research is required to enhance understanding of the dynamic rules and safety risks associated with venting operations for supercritical CO2 pipelines with topographic relief. Methods Using OLGA, a physical model was developed for venting valve chambers at both ends of supercritical CO2 pipelines with topographic relief. A dynamic simulation analysis of pipeline venting was conducted, revealing the physical nature of the low-temperature phenomenon in the main pipeline during venting. Key issues in the venting process of the supercritical CO2 pipeline with topographic relief were discussed, focusing on the effects of topographic relief on phase transition, low-temperature risks, and dry ice formation. Finally, a safe venting scheme for backpressure control was suggested. Results The venting of supercritical CO2 pipelines with topographic relief should avoid high pressure and low temperatures as much as possible; appropriate venting pipe diameter and opening need to be designed to prevent risks such as low-temperature brittle fracture and dry ice formation; the suggested venting scheme was effective under specific terrain conditions, addressing extremely low temperatures in low-lying sections during main pipeline venting while minimizing harm at the venting outlet. Conclusion The research results offer theoretical backing for the safe venting process design and engineering construction of supercritical CO2 pipelines with topographic relief, holding practical value for engineering applications and contributing to ensuring the safe and efficient transmission of CO2 pipelines.